2019
DOI: 10.14739/2310-1210.2019.6.186484
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of interleukin-4 gene (C-589T, rs2243250) polymorphism in children with bronchial asthma and allergic rhinitis with isolated or allergic rhinitis-induced comorbid malocclusion

Abstract: A -research concept and design; B -collection and/or assembly of data; C -data analysis and interpretation; D -writing the article; E -critical revision of the article; F -final approval of the article Purpose. To determine the frequency of interleukin-4 (IL-4) (C-589T, rs2243250) single nucleotide polymorphism in children with bronchial asthma (BA) and allergic rhinitis (AR) and with isolated or allergic rhinitis-induced comorbid malocclusion. Materials and methods.Single nucleotide polymorphism of the IL-4 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Shumna et al analyzed the relationship of the IL-4 T589C polymorphism with bronchial asthma, allergic rhinitis, and orthodontic pathology and concluded that the CC genotype of the IL-4 gene is associated with bronchial asthma (OR = 4.31; 95% CI = 1.63–11.36; p = 0.002) and allergic rhinitis (OR = 4.32; 95% CI = 1.04–7.81; p = 0.04) [ 32 ]. The TT genotype showed a predisposition to the development of orthodontic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Shumna et al analyzed the relationship of the IL-4 T589C polymorphism with bronchial asthma, allergic rhinitis, and orthodontic pathology and concluded that the CC genotype of the IL-4 gene is associated with bronchial asthma (OR = 4.31; 95% CI = 1.63–11.36; p = 0.002) and allergic rhinitis (OR = 4.32; 95% CI = 1.04–7.81; p = 0.04) [ 32 ]. The TT genotype showed a predisposition to the development of orthodontic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…25, № 3 нетическую предрасположенность, нарушение регуляции и синтеза цитокинов [1,2,4,5,6,7,9,10]. Бронхиальная астма относится к многофакторным воспалительным заболеваниям, имеет сложную этиологию, зависящую от множества генетических факторов, контроль которого требует понимания различных механизмов иммунопатогенеза [3,8,11,12,13,14]. Мутации в генах цитокинов, определяющие дефекты продукции и рецепции отдельных цитокинов, составляют значительную часть иммуноопосредованных механизмов развития и прогрессирования патологических процессов при аллергических заболеваниях [1].…”
Section: генотипы цитокинов у детей с бронхиальной астмойunclassified